A green approach to the microwave-assisted synthesis of flower-like ZnO nanostructures for reduction of Cr(VI). Issue 1 (7th February 2019) - Al Marzouqi, Faisal; Al Adawi, Hanan; Qi, Kezhen; Liu, Shu-yuan; Kim, Younghun; Selvaraj, Rengaraj
Abstract: Zinc oxide nanostructures with different morphologies were prepared via a microwave-assisted method and used as photocatalysts for reduction of chromium(VI) under ultraviolet-B illumination. X-ray diffraction revealed that as-made ZnO samples have wurtzite hexagonal structure. Scanning electron microscopy demonstrated that the morphology of the ZnO crystals could be easily modified from star-shaped to chrysanthemum flower-like structure by changing the ratio of zinc nitrate and sodium hydroxide. X-ray photoelectron spectroscopy and energy dispersive X-ray analysis confirmed the stoichiometry of pure ZnO. Its optical properties were also investigated by UV-Vis diffuse reflectance spectroscopy, which indicated that the prepared ZnO possessed a band gap value of 3.2 eV. Photocatalytic activity studies revealed that the ZnO (1:6) (1 × 10 −3 mol zinc nitrate: 6 × 10 −3 mol sodium hydroxide) catalyst exhibited a significantly faster reduction rate of Cr(VI) compared to ZnO (1:5) and ZnO (1:4). More than 95% of Cr(VI) at a concentration of 10 mg/L has been reduced to Cr(III). Graphical Abstract: Research highlights: Investigate the use of microwave-assisted method as rapid approach to synthesize ZnO nanostructure. Study the impact of the pH level on the morphology of ZnO samples. Systematic evaluation of physical and chemical properties of prepared ZnO samples. Evaluation of the photocatalytic reduction of chromium(VI) to chromium (III) under UV-B light irradiation.